2020
DOI: 10.1021/acs.chemrev.9b00629
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Bioinspired Inorganic N–N Bond-Forming Reactions

Abstract: The metallobiochemistry underlying the formation of the inorganic N-N-bond-containing molecules nitrous oxide (N 2 O), dinitrogen (N 2 ), and hydrazine (N 2 H 4 ) is essential to the lifestyles of diverse organisms. Similar reactions hold promise as means to use N-based fuels as alternative, carbon-free energy sources. This review discusses research efforts to understand the mechanisms underlying biological N-N bond formation in primary metabolism and how the associated reactions are tied to energy transductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 534 publications
(1,183 reference statements)
0
75
0
Order By: Relevance
“…NO reductase, are well known. [50] Seminal work by Tolman and Karlin has shown that synthetic copper complexes can promote a similar NO • coupling reaction and generate N2O. We now demonstrate such a dicopper-promoted NO • process could be a potential strategy to facilitate the storage of NO • as S-nitrosothiol.…”
Section: Resultsmentioning
confidence: 60%
“…NO reductase, are well known. [50] Seminal work by Tolman and Karlin has shown that synthetic copper complexes can promote a similar NO • coupling reaction and generate N2O. We now demonstrate such a dicopper-promoted NO • process could be a potential strategy to facilitate the storage of NO • as S-nitrosothiol.…”
Section: Resultsmentioning
confidence: 60%
“…It thus behaves as an Fe(II) aminyl 57 and is readily trapped by ArO• or scavenges H• atoms from appropriate donors (THF coordinated to Li, for example). Our attempts to generate it in the absence of such traps were motivated by the possibility that it might dimerize through N-N bond formation, which has been proposed in a variety of catalytic cycles, 68 and in particular for ammonia oxidation catalysts operating through the hydrazine pathway (Scheme 1). 9,10 Indeed, such a process has recently been observed in a related d 7 Ni(III) system.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…In our experiments, variations in the 15 ε(NH 4 + ) values were observed in mainstream and enrichment experiments, where the anammox bacteria population is expected to be similar, which also argues against species dependence. Indeed, the Hzs enzyme seems well conserved across anammox clades 50 , and, therefore, the ammonium N isotope effect variation observed here cannot be attributed to sequence variations, and is more likely due to the changing experimental conditions (NH 4 + concentrations), as discussed above.…”
Section: Discussionmentioning
confidence: 66%